Portable X-ray fluorescence analysis of Armenian obsidian sources - Juharyan, Aleksan (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
During recent years the most effective and practical method for volcanic glass, commonly called obsidian sourcing is portable X-ray fluorescence (pXRF). In spite of the reliability of this method and the growing demand in recent years, the Armenian obsidian sources have been analyzed by using the above-mentioned analytical method only in the few studies.